SOCIOLINGUISTIC CHARACTERISTICS OF TOPONYMS OF FERGANA REGION (Scientific journal of the Fergana State University, 2024)
The article analyzes issues such as the sociolinguistic features of the toponyms of the Fergana region, the language reflection of the changes in the life of the society when naming them. If we pay attention to the creation of toponyms and their nominative-motivational features, it can be seen that even the most random name was created due to social need and necessity in certain periods. In some cases, the name given to one object is changed to different names at certain stages based on the specific social necessity of the time. That is why, if we pay attention to the naming of many mountains, lakes, rivers, or cities and villages whose creation goes back to long periods, we can see that they were called by several names in different historical periods and stages. In other words, the emergence, stagnation or, on the contrary, the exchange of toponyms, the occurrence of various changes in their meaning, shows that it is inextricably linked with the fate of society. In addition, any toponymic change takes place within the framework of the language laws in force in the society. Based on this, it can be said that toponyms are viable and stable as the lexical wealth of the language, but they change according to the historical conditions and ideological point of view. All this is reflected in its lexical layer and shows the need for a sociolinguistic approach to the study of toponyms.